2023
DOI: 10.1017/s1754470x22000642
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s been quite a poor show’ – exploring whether practitioners working for Improving Access to Psychological Therapies (IAPT) services are culturally competent to deal with the needs of Black, Asian and Minority Ethnic (BAME) communities

Abstract: Cultural competency is a core clinical skill. Yet, psychological therapists may be inadequately trained to deal with the needs of service users from Black, Asian and Minority Ethnic (BAME) backgrounds. This can lead to dissatisfaction with mental health services, disengagement from therapy, and poorer treatment outcomes when compared to the White British population. The aim of this study was to explore whether practitioners working for Improving Access to Psychological Therapies (IAPT) services are culturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…Research shows that ethnic matching can be an effective approach for tailoring therapy (Arundell et al , 2021) as it enables practitioners to identify the needs of service users from ethnic minorities by improving communication and facilitating rapport (Alegría et al , 2013; Granek et al , 2020). Similar to the findings of Faheem (2023b), BAME therapists were better able to empathise with their patients if they shared an ethnic identity because they were familiar with their family dynamics and upbringing. Although PWP participants of the current study did not raise any issues of ethnic matching, recognizing if a BAME service user prefers seeing a non-BAME therapist due to fear of judgement or due to discussing sensitive topics is also a crucial cultural competency skill (Faheem, 2023b).…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Research shows that ethnic matching can be an effective approach for tailoring therapy (Arundell et al , 2021) as it enables practitioners to identify the needs of service users from ethnic minorities by improving communication and facilitating rapport (Alegría et al , 2013; Granek et al , 2020). Similar to the findings of Faheem (2023b), BAME therapists were better able to empathise with their patients if they shared an ethnic identity because they were familiar with their family dynamics and upbringing. Although PWP participants of the current study did not raise any issues of ethnic matching, recognizing if a BAME service user prefers seeing a non-BAME therapist due to fear of judgement or due to discussing sensitive topics is also a crucial cultural competency skill (Faheem, 2023b).…”
Section: Discussionsupporting
confidence: 69%
“…Due to the ethnic differences, PWPs felt compelled to hear and address service users’ experiences of being part of ethnic minorities, to prove that they are unbiased and objective in their practice. This contrasts Faheem (2023b), where White therapists are reported to have been reluctant to see BAME patients because they felt afraid to deal with individuals from different ethnic backgrounds. Similarly, previous research has also shown that White therapists feel uncomfortable with BAME service users, particularly because they lack the training needed to equip them to address cultural differences in therapy (Knox et al , 2003; Patel, 2014).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations